The Development of Protocol Educational Game Application to Enhance English Vocabulary Learning of Mathayomsuksa 5 Students - Sulaiman, Fraydau (Suan Dusit Graduate School Academic Journal, 2023)
This research aimed to develop the protocol educational game application to enhance English vocabulary learning in order to meet the efficacy performance at E1/E2 = 85/ 85 criterion, to compare the pre-test and post-test scores after learning with the game application, and to evaluate the students’ satisfaction towards the game application. The application was evaluated by both contents and media experts. Pretest and posttest exam paper for targeted vocabularies and the satisfaction evaluation form were used as the research tools to collect data from 20 samples who were chosen from Mathayomsuksa 5 students from Demonstration School of Yala Rajabhat University with purposive sampling method. The data were analyzed using basic statistics and nonparametric statistics (Wilcoxon Matched-Pairs Signed-Rank (WSR) Test). The research findings showed that the game application had the efficiency level of 85.69/85.42, which met the set criterion. Moreover, the post-test’s mean scores after learning with the game application were significantly higher than the pre-test’s mean scores at the statistical significance level of .05. The results also showed that the students were most highly satisfied towards the protocol application at the mean score of 4.64.